Defoliacion artificial para estimar perdidas por danos foliares en frijol (Phaseolus vulgaris) - Gálvez E., Guillermo E.; Galindo, J.J.; Álvarez, G.G. (1977)
Bean diseases such as rust (Uromyces phaseoli var. typica), web blinght (Thanatephorus cucumeris) and angular leaf spot (Isariopsis griseola), not only destroy plant foliage but also cuase physiological damage. To determine yield losses, the cv. ICA-Gualì and porrillo sintetico were artificially defoliate to stimulate disease attack. Twenty, 40, 60, 80 or 100 percent of the leaf surface area was removed at one of the following plant development stages: formation of 1st trifoliate leaves, initiation of flowering, pod formation or initiation of maturation (60 days after planting). In 3 replications, yield losses from 100 percent defoliation were greater at initiation of flowering and pod formation; losses were 59 and 77 percent, respectively, for ICA- Guali. For Porrillo Sintetico, losses were 60 and 73 percent in the same periods. During the formation of 1st trifoliate leaves, 100 percent defoliation decreased yields of ICA Guali 34 percent and those of Porrillo sintetico 49 percent. Total defoliation in stage of initiation of maturation decreased yield 20 percent in both cv. (AS)